Profile and Characteristics of Analgesic Use in Myalgia Cases at Soromandi Health Center - Rahmatillah, Rahmatillah (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Myalgia is a common muscle pain condition that often requires pharmacological analgesic therapy for pain management. This study aims to determine the profile and characteristics of analgesic use in myalgia patients at Puskesmas Soromandi. Data were obtained through a retrospective study of patient medical records from January to December 2023, using consecutive sampling method. The data were analyzed descriptively and presented in tables and percentages. The results show that the most common demographic groups using analgesics for myalgia were patients aged 46-65 years (46.53%), female (57.4%), and farmers (48.5%). The most frequently used analgesic was ibuprofen 400 mg (40.59%), which was more often combined with supplements rather than used as monotherapy. The most common duration for analgesic administration was 5 days (56.43%). Conclusion: Myalgia patients are generally aged 46-65 years, with a predominance of females and farmers. Ibuprofen and a 5-day duration of analgesic treatment are the most frequently applied approaches in myalgia cases at Puskesmas Soromandi.